2023
DOI: 10.1007/s10557-023-07534-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CYP2C19 Genotype on Efficacy and Safety of Clopidogrel-based Antiplatelet Therapy in Stroke or Transient Ischemic Attack Patients: An Updated Systematic Review and Meta-analysis of Non-East Asian Studies

Sarah Cargnin,
Federica Ferrari,
Salvatore Terrazzino

Abstract: Purpose Inconclusive and limited results have been reported on the clinical utility of CYP2C19 genotyping in stroke/TIA patients of non-East Asian ancestries. We herein performed an updated systematic review and meta-analysis to quantitatively estimate the association of CYP2C19 loss-of function (LOF) status with efficacy and safety of clopidogrel-based antiplatelet therapy in non-East Asian patients affected by stroke or TIA. Methods A comprehensive searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…However, the risk of severe or moderate bleeding events did not differ between these two treatment groups (0.3% vs. 0.3%), although total bleeding events were slightly higher in ticagrelor treatment group compared with clopidogrel treatment group (5.3% vs. 2.5%). 52 It is believed that the CPIC guideline should update the prescribing recommendations including stroke patients since the robust evidence established in this analysis, along with other available evidence, 2,16 warrants this.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, the risk of severe or moderate bleeding events did not differ between these two treatment groups (0.3% vs. 0.3%), although total bleeding events were slightly higher in ticagrelor treatment group compared with clopidogrel treatment group (5.3% vs. 2.5%). 52 It is believed that the CPIC guideline should update the prescribing recommendations including stroke patients since the robust evidence established in this analysis, along with other available evidence, 2,16 warrants this.…”
Section: Discussionmentioning
confidence: 89%
“…Another very recent meta-analysis was published to validate the associations between carriers of CYP2C19 LoF alleles and the risk of recurrent stroke in non-East Asian populations but this analysis did not consider other populations. 16 Thus, the only available well-established meta-analysis was published in 2017, which included 15 studies with 4762 stroke/TIA patients from all ethnic groups, including Asians, Europeans, Africans, and other ethnicities. 2 Although it was a well-established analysis, since then, many more studies have appeared in the literature; therefore, there is a need to update the meta-analysis of the literature.…”
Section: Introductionmentioning
confidence: 99%
“…he has only one functional CYP2C19 allele), which means that the conversion of clopidogrel to the active metabolite will be suboptimal. A recent systematic review and meta-analysis of non-East Asian studies showed that individuals carrying CYP2C19 loss-of-function alleles on clopidogrel were at an increased risk of stroke (relative risk 1.68) when compared to noncarriers [78]. This was also observed in patients of European ancestry carrying CYP2C19 loss-offunction alleles (relative risk 2.69).…”
Section: Case Studymentioning
confidence: 98%